Pigmentation Disorders - Etiology and Recent Advances in Treatments 2023
DOI: 10.5772/intechopen.106791
|View full text |Cite
|
Sign up to set email alerts
|

Skin Depigmenting Agents: Where Do We Stand?

Abstract: Skin hyperpigmentary disorders are frequent and psychologically disturbing conditions for patients. Skin depigmenting agents have been widely used for the treatment of such disorders. The most efficacious depigmenting agents, such as hydroquinone and the Kligman’s formula, are associated with long-term side effects, and safer skin depigmenting agents, such as kojic acid, arbutin, and niacinamide, might suffer from a significantly lower depigmenting efficacy. Therefore, there is still a need for safe and simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…25 Studies have shown that peroxidase enzymes have the capability to metabolize isoniazid, which may contribute to the hypopigmentation that is sometimes observed in individuals taking the medication. 13 This inhibition of peroxidase activity could prevent the conversion of tyrosine to dopaquinone and, ultimately, melanin, leading to a decrease in melanin production. 13 Topical isoniazid was previously shown to exert skin depigmenting action in animal models.…”
Section: Ta B L E 4 Mean Modified Melasmamentioning
confidence: 99%
See 3 more Smart Citations
“…25 Studies have shown that peroxidase enzymes have the capability to metabolize isoniazid, which may contribute to the hypopigmentation that is sometimes observed in individuals taking the medication. 13 This inhibition of peroxidase activity could prevent the conversion of tyrosine to dopaquinone and, ultimately, melanin, leading to a decrease in melanin production. 13 Topical isoniazid was previously shown to exert skin depigmenting action in animal models.…”
Section: Ta B L E 4 Mean Modified Melasmamentioning
confidence: 99%
“…13 This inhibition of peroxidase activity could prevent the conversion of tyrosine to dopaquinone and, ultimately, melanin, leading to a decrease in melanin production. 13 Topical isoniazid was previously shown to exert skin depigmenting action in animal models. [12][13][14] In a study involving six black male guinea pigs, daily application of a 10% isonicotinic acid hydrazide cream on one ear and topical placebo on the contralateral ear for 10 consecutive days resulted in a significant reduction in melanin index (p < 0.005) without any adverse effects or irritation.…”
Section: Ta B L E 4 Mean Modified Melasmamentioning
confidence: 99%
See 2 more Smart Citations
“…Melasma is a prevalent hyperpigmentation disorder that is frequently triggered by hormonal changes [15]. It can lead to emotional distress, diminished self-esteem, and feelings of frustration due to the noticeable visibility of the condition [17,18]. Addison's disease is a hormonal disorder that can cause increased melanin production.…”
Section: Introductionmentioning
confidence: 99%